Values and reality - Ward, Leo (Sheed & Ward, 1935)
Value, Reality, and Desire is an extended argument for a robust realism about value. The robust realist affirms the following distinctive theses. There are genuine claims about value which are true or false--there are facts about value. These value-facts are mind-independent - they are not reducible to desires or other mental states, or indeed to any non-mental facts of a non-evaluative kind. And these genuine, mind-independent, irreducible value-facts are causally efficacious. Values, quite literally, affect us.